Mechanical, forming and biological properties of Ti-Fe-Zr-Y alloys prepared by 3D printing. Issue 7 (July 2019) - Han, Liying; Wang, Cunshan; Li, Zhengwei
Abstract: Biomedical Ti-Fe-Zr-Y alloys were prepared by 3D printing on pure titanium substrate. The influences of Zr on mechanical, forming, and biological properties of the alloys were investigated in detail. The results showed that with increasing the Zr addition, the surface roughness, friction coefficient and worn volume decrease at first and then increase, the lowest values obtained at 5.86 at.% Zr addition. The ultimate compression stress and specific strength gradually decrease. The studied alloys have no cytotoxicity. They can promote the early adhesion and proliferation of cells. The eutectic alloy with 5.86 at.% Zr addition has the best ability of apatite deposition, it exhibits a better comprehensive performance among the studied alloys, which is superior to the Ti70.5 Fe29.5 and Ti-6Al-4 V alloys.